Implantable polyurethaneurea medical devices: synthesis, surface modification,bioсompatibility - Yakusheva, D.E.; Karpunina, T.I.; Godovalov, A.P.; Astafeva, S.A.; Slobodinyuk, A.I. (Perm Federal Research Centre Journal, 2021)
Four polyurethane samples have been synthesized. The structure of the materials has been studied by IR ATR spectroscopy. The biocompatibility of the initial materials was evaluated by in vitro hemolysis by photometric method. Polyurethane urea SPUM-1 has been found to be the most hemocompatible. Two groups of surface modification methods have been developed, a number of samples with organic moieties and radicals grafted to the surface of SPUM-1 have been obtained. It has been found that the introduction of long-chain hydrocarbon radicals and an aldehyde group into the surface layer structure results in a decrease in erythrocyte lysis. At СNaCl = 0,45% the erythrocyte lysis in the presence of these samples decreases by 20–25% compared to the initial sample. Biofilm formation on polyurethane samples has been studied by microplate photometry. It has been found that the presence of a chemically bonded quaternary dioctylammonium on the surface leads to a significant decrease in the a ount of adhered biofilm, since the protein content on the surface after incubation with s. epidermidis is 10 times lower than that of the initial sample. The biocompatibility of the initial and modified cord samples has been studied in vivo using experimental animals (rats). It was shown that both the initial and modified materials have a relatively good biocompatibility. According to the results of histological analysis, the best results demonstrated the sample with grafted aldehyde groups. Biocompatibility of implantable materials was studied by original technique using human blood leukocytes. The differences in the individual reactivity of blood cells taken from different donors have been found.